2014
DOI: 10.1590/0104-1169.0029.2484
|View full text |Cite
|
Sign up to set email alerts
|

Music and 25% glucose pain relief for the premature infant: a randomized clinical trial

Abstract: OBJECTIVE: to analyze the total Premature Infant Pain Profile scores of premature infants undergoing arterial puncture during music and 25% glucose interventions, and to assess their association with neonatal and therapeutic variables. METHOD: a randomized clinical trial with 80 premature infants; 24 in the Experimental Group 1 (music), 33 in the Experimental Group 2 (music and 25% glucose), 23 in the Positive Control Group (25% glucose). All premature infants were videotaped and a lullaby was played for ten m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
(12 reference statements)
2
25
1
1
Order By: Relevance
“…Although there were no significant physiological differences between the groups, there was a significant decrease in the RRs of infants who listened to their mothers’ music before and after the heel stick, which is supported by some earlier studies and not others . The inconsistent results in our case may be due to the duration of the stimulus provided, and further studies that evaluate the impact of specific elements of music are suggested.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although there were no significant physiological differences between the groups, there was a significant decrease in the RRs of infants who listened to their mothers’ music before and after the heel stick, which is supported by some earlier studies and not others . The inconsistent results in our case may be due to the duration of the stimulus provided, and further studies that evaluate the impact of specific elements of music are suggested.…”
Section: Discussionsupporting
confidence: 78%
“…The fact that music may help reduce pain during a heel stick is supported by most previous studies and not supported in a few others . For example, a triple‐blind trial that divided 80 preterm infants into three groups – 24 in an experimental music group one, 33 in an experimental music plus 25% glucose group and 23 in a control group with 25% glucose – found no significant association between pain scores and intervention groups . The incongruous findings in these studies may be due to the differences in the duration and the loudness of the musical stimuli, the kind of music provided and the method of pain assessment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Musical intervention is a therapeutic resource that has been increasingly used in nursing care as a complementary therapy to promote relaxation, emotional and spiritual comfort, distraction, wellness sensation 4 and relief of pain in hospitalized patients 5 . Despite the use of musical intervention by nursing, the therapeutic effectiveness of music has not yet been clearly established 6 .…”
Section: Introductionmentioning
confidence: 99%